Causes of incestuous rape in Zimbabwe: a case study of the Epworth community in Harare - Sukdaven, Maniraj (Stellenbosch theological journal, 2023)
This article unveils the causes of incestuous rape in the Epworth community of Zimbabwe. It was premised on a feminist theoretical framework which was applied in light of the perspectives of African Christians, Shona indigenous religious people, and Shona culture. The research hopes to serve as a resource for victims of incestuous rape, scholars, religious leaders, community leaders, the government, those who sympathetically seek to support incestuous rape victims, and those who seek to become a voice of the voiceless to treat incestuous rape as a serious problem that needs serious attention. It addresses three major objectives: (1) to unveil how Epworth residents construe incestuous rape; (2) to expose the prevalence of incestuous rape cases in Epworth; and (3) to highlight the factors which lead to the occurrences of incestuous rape cases in Epworth. The study has established that the causes of incestuous rape in Epworth may vary, but most notably, are ascribed to some cultural and religious beliefs, practices, and perspectives.